2019
DOI: 10.1039/c8cc07322h
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis of glycerolipids containing simple linear acyl chains or aromatic rings and evaluation of their Mincle signaling activity

Abstract: The synthesized glycerolipid derivatives possessing simple alkyl chains can stimulate a Mincle-mediated signaling assay relevant for the innate immune system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Thus, the results suggested that the diester structure motif such as in 2 a and 2 b is not a sufficient ligand motif to elicit potent signaling activity. This result is consistent with the dimanosyl‐oxystearates, the partial structure of the mannosyloxymannitol glycolipid, which showed signaling activity [28] . The binding mode of mannosyloxymannitol glycolipid and Mincle is still unclear, but this result could be a clue to the mechanism of the interaction between mannosyloxymannitol glycolipid and Mincle.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Thus, the results suggested that the diester structure motif such as in 2 a and 2 b is not a sufficient ligand motif to elicit potent signaling activity. This result is consistent with the dimanosyl‐oxystearates, the partial structure of the mannosyloxymannitol glycolipid, which showed signaling activity [28] . The binding mode of mannosyloxymannitol glycolipid and Mincle is still unclear, but this result could be a clue to the mechanism of the interaction between mannosyloxymannitol glycolipid and Mincle.…”
Section: Resultssupporting
confidence: 85%
“…Various Mincle ligands have been reported including the glycolipids such as 6‐acylated glycosides, [11] glucosyl diacylglycerides, [12–14] other trehalose esters, [15–24] and also recently found cholesteryl acyl α‐glucosides (αCAG) [25–27] . We previously reported that 1‐monoacylglycerol harbors relationships between activity and acyl chain length [28] . Furthermore, Mincle recognized endogenous ligands such as β‐GluCer [29] and cholesterol crystals [30] .…”
Section: Introductionmentioning
confidence: 96%
“…C 8 GlcC 8 This work builds on related efforts exploring structure activity relationships of acyl-hexoses (as analogues of glucose monomycolate), 15,16 glycosyloxy-stearates (as analogues of the mannosyloxymannitol glycolipid from Malassezia pachydermatis), 28 glycerolipids (as analogues of glycerol monomycolate), 27,29 mono- 13 and diacyl trehaloses, 12,30 and lipidated diaroyltrehaloses (as analogues of brartemicin). 14,31 The present work is notable for the simplicity of the resulting agonists and the fact that unlike acyl-hexoses they exist as single stereoisomers.…”
Section: Nfat-gfp (%)mentioning
confidence: 99%
“…This trend in activity is reminiscent of the ability of trehalose mono- 13 and diesters 12 to activate macrophages, wherein the C22 compounds were more potent than the C26 analogues, and a homologous series of acyl glycerols, where potency peaked at C28. 27 Fig. 2 Agonism of Mincle signalling by unsubstituted octyl or lauryl -D-glucopyranosides or straight-chain 6-O-acyl variants.…”
mentioning
confidence: 99%
“…25 As our analogues are alkylated cholesterol derivatives, and signal through both mouse and human Mincle, it seems unlikely that the cholesteryl Please do not adjust margins Please do not adjust margins moiety binds at the CRAC site of Mincle and is likely simply a surrogate for a lipid group. This work builds on related efforts exploring structure activity relationships of acyl-hexoses (as analogues of glucose monomycolate), 15,16 glycosyloxy-stearates (as analogues of the mannosyloxymannitol glycolipid from Malassezia pachydermatis), 28 glycerolipids (as analogues of glycerol monomycolate), 27,29 mono- 13 and diacyl trehaloses, 12,30 and lipidated diaroyltrehaloses (as analogues of brartemicin). 14,31 The present work is notable for the simplicity of the resulting agonists and the fact that unlike acyl-hexoses they exist as single stereoisomers.…”
mentioning
confidence: 99%